Seed collecting and identification - Gunn, Charles R.
Seed Biology: Insects, and Seed Collection, Storage, Testing, and Certification, Volume III brings together a large body of important information on seed biology. The book describes seed collection, identification, storage, testing, and certification. It also considers insects that directly affect seeds, seed-producing organs, or seed-bearing structures of plants. Organized into six chapters, this volume begins by outlining man's dependency on seeds as source of food, fiber, spices, beverages, oils, vitamins, and drugs. Harmful effects of seeds are also mentioned. Separate chapters focus on seed development, dissemination, germination (including metabolism, environmental control, internal control, dormancy, and seed and seedling vigor), protection from diseases and insects, longevity, and deterioration. The book concludes with a discussion on the certification of field and tree seeds, the Organization for Economic Cooperation and Development certification schemes, and trends in seed certification.
Keywords: SEED; SEED STORAGE